Model Prediksi Perubahan Anggaran Belanja Daerah Pada Kabupaten Kota di Kalimantan Selatan - Mochamad Novelsyah; Wahyudin Nor; Rasidah (Politeknik Caltex Riau, 2022)
This study aimed to examine and analyze the effect of Income Variance, Expenditure Variance, Financial Autonomy, and Surplus Accumulation on the prediction model of Regional Budget Changes in districts and cities in the province of South Kalimantan. The data used in this study is secondary data derived from reports on budget realization and regional expenditure budgets. The population in this study were all districts and cities in the province of South Kalimantan for the 2015-2019 period. The number of districts and cities in this study were 12 local governments with an observation period of five years. The data analysis technique used is multiple linear regression analysis using the SPSS Version 25 program. The test results show that the Income Variance, Expenditure Variance, and Accumulated Surplus significantly affect Changes in the Regional Budget. In contrast, the Financial Independence variable has no significant effect on Changes in the Regional Budget.